Empowering Arabic Learning Through Mahfudhot Poster Innovation - Khoirunnisa, Imanda Aflahat; HIKMAH, KHIZANATUL (Indonesian Journal of Islamic Studies, 2024)
The abstract presents the importance of visual design, particularly in educational contexts, for enhancing learning motivation and comprehension. It highlights the potential of mahfudhot posters, combining Arabic language learning with visually stimulating elements. The study aimed to investigate the impact of mahfudhot posters on student learning motivation, disciplinary values, and philosophical insight. The research employed qualitative methods to design and implement the mahfudhot poster about Learning Motivation. Results indicate that incorporating mahfudhot posters in Arabic language learning fosters increased enthusiasm and comprehension among students. The findings suggest the value of integrating visual design strategies into educational materials to promote learning motivation and holistic understanding. Highligh: Visual design enhances learning: Visual elements engage learners across age groups. Mahfudhot posters in education: Combining Arabic learning with visual stimuli. Impact on student motivation: Study explores poster's role in instilling discipline. Keywoard: Visual design, Mahfudhot posters, Learning motivation, Arabic language, Educational materials